Female Sexual Dysfunction and Diabetes: A Systematic Review and Meta‐Analysis. (24th January 2013) - Pontiroli, Antonio E.; Cortelazzi, Donatella; Morabito, Alberto
Abstract Introduction Sexual dysfunction is reported in diabetic women (female sexual dysfunction [FSD]). Aim To examine the frequency of FSD in diabetic women, and its clinical or metabolic correlates, through meta‐analysis of available studies. Methods We searched in MEDLINE, EMBASE, Cochrane Library, and in reference lists of articles and systematic reviews; we considered human clinical studies published as full articles reporting on FSD in diabetic and control women. In total, we considered 26 studies, including 3, 168 diabetic and 2, 823 control women. Main Outcome Measures Frequency of FSD and score of Female Sexual Function Index (FSFI) as a function of study size, patient details (age, body mass index [BMI], duration of diabetes, metabolic control [HbA1c], chronic complications, Beck Depression Inventory [BDI] score). Results Frequency of FSD was higher in type 1 (OR [95%CI] 2.27 [1.23, 4.16]), in type 2 diabetes (2.49 [1.55, 3.99]), and in "any diabetes" (type 1 and 2) women (2.02 [1.49, 2.72]) than in controls for any duration of diabetes. FSFI was lower in type 1 (−0.27 [−0.41, −0.12]), in type 2 diabetes (−0.65 [−0.75, −0.54]), and in "any diabetes" women (−0.80 [−0.88, −0.71]) than in controls. Depression was significantly more frequent in diabetic than in control women. At meta‐regression only BMI was significantly associated with effect size (P = 0.005). At weighed regression, the only significant association was found between age and FSFI (P = 0.059). The limitations were as follows: only studies of observational nature were available, and heterogeneity was seen among studies. Conclusions FSD is more frequent in diabetic than in control women, but it is still poorly understood; low FSFI is associated with high BMI. Further studies are necessary to better understand risk factors for FSD in diabetic women.